Progress in understanding the genetics of Bronchopulmonary Dysplasia - Shaw, Gary M. (2013)
Bronchopulmonary dysplasia (BPD) is the most common chronic lung disease of infants. Its treatment imposes considerable health care burden and costs in the perinatal and early childhood period and patients are usually left with life-long deficits in lung function. Evidence exists for different pathophysiologic pathways that can promote the structural changes that characterize BPD, including the impairment in alveolarization; however, there is increasing interest regarding heritable factors that may predispose very low birth weight infants to BPD. Our review focuses on recent publications that have investigated genetic factors that may potentially contribute to such reported heritability. These publications point us towards some possible genomic candidates for further study, but certainly do not identify any particular gene or gene pathway that would be inferred to be contributing substantially to the underlying etiology of BPD.